The cinderella effect : renting in the Portuguese fashion industry : exploring perceptions, attitudes, and willingness to rent clothing of Portuguese consumers alongside the moderated-moderation effect of shopping motivations and personal innovativeness - Fontinha, Inês Cerveira Nunes (2023)
Over the years, the fashion industry has become one of Earth's most significant and dangerous polluting forces. Unmeasured use of natural resources, minimal product life cycles, and increasingly low product prices due to inhumane working conditions have awakened consumers to demand better industry practices and sustainable alternatives. As a response, collaborative consumption models emerged. Namely, clothing rental platforms allow consumers to wear the latest fashion trends without paying the total price of the pieces and still engage in a more conscious consumption practice, which reduces overconsumption and waste. Fashion rental platforms are a growing international trend. However, it still needs to be unveiled in the Portuguese market. Therefore, this dissertation aims to understand Portuguese consumers' perceptions and attitudes towards this business model, alongside their willingness to rent clothing. An experimental study investigated the effect of the type of occasion wear on perceptions, attitudes, and willingness to rent clothes for special occasions versus everyday while testing for the moderating role of shopping motivations and personal innovativeness on that relationship. Moderated-moderation findings show that consumers in the Portuguese market have positive perceptions, attitudes, and willingness to rent clothing. This effect is often motivated by hedonic than utilitarian shopping motivations. However, the type of preferred clothing varies according to the level personal innovativeness of consumers. The present dissertation contributes to the collaborative consumption, personal innovativeness, and motivations literature with theoretical and managerial implications that can shape the path for fashion rental companies in Portugal.